Differences in the nutritional content of baby and toddler foods with front-of-package nutrition claims issued by manufacturers v. governments/health organizations. Issue 1 (10th January 2014) - Metcalfe, Amy; Elliott, Charlene
Abstract: Objective: Nutritional information panels are required on all packaged food products in the USA, yet are perceived as difficult to use by consumers. Nutritional symbols have been developed by various groups to assist consumers in making healthier food purchases. Different nutritional criteria are used depending on the authorizing body of these symbols. The present study assesses the nutrient profile of baby and toddler foods in light of their accompanying nutritional symbols. Design: Kruskal–Wallis and χ 2 tests were used to assess differences in the nutritional content of products based on the presence and issuing body of nutritional symbols. Setting: Nine grocery, drug and department stores in Philadelphia, PA, USA. Subjects: Two hundred and forty packaged baby and toddler foods. Results: Products whose nutritional symbol was issued by government/health professionals contained significantly more Ca ( P = 0·002), fibre ( P = 0·001), protein ( P = 0·005), vitamin A ( P = 0·011), vitamin C ( P < 0·001) and Zn ( P < 0·001) and less sugar ( P = 0·004) per serving than products without a nutritional symbol and products whose nutritional symbol was issued by the manufacturer. Conclusions: Products with a nutritional symbol issued by government/health professionals were healthier than foods with nutritional symbols issued by the manufacturer directly and foods with no nutritional symbols.